2015
DOI: 10.4085/1062-6050-50.10.01
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Directors' Barriers to Hiring Athletic Trainers in High Schools

Abstract: Context In its best-practices recommendation, the Inter-Association Task Force for Preventing Sudden Death in Secondary School Athletics Programs urged all high schools to have a certified athletic trainer (AT) on staff. Despite the recommendation, many high schools lack the medical services of an AT. Objective To examine the barriers that athletic directors (ADs) face in hiring ATs in public high schools and in providing med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Savings of both public and private healthcare dollars will further spur public-private cooperation in financing the school-employment model of AT services (Hambleton et al 2012). In fact, researchers across the nation have urged all stakeholders to advocate for each state’s funds to support employing ATs in high schools (Hambleton et al 2012; Mazerolle et al 2015). We echo this nationwide advocacy by providing evidence from our innovative study.…”
Section: Discussionmentioning
confidence: 99%
“…Savings of both public and private healthcare dollars will further spur public-private cooperation in financing the school-employment model of AT services (Hambleton et al 2012). In fact, researchers across the nation have urged all stakeholders to advocate for each state’s funds to support employing ATs in high schools (Hambleton et al 2012; Mazerolle et al 2015). We echo this nationwide advocacy by providing evidence from our innovative study.…”
Section: Discussionmentioning
confidence: 99%
“…This stems in part from a persistent belief that a coach can provide medical care in the place of ATs. 19 Studies have shown a low level of knowledge by coaches concerning health-related issues such as management and recognition of concussions, first aid, and hydration strategies. 12,13,20,29 Coaches do not receive the appropriate training or education to handle such emergency situations.…”
Section: Discussionmentioning
confidence: 99%
“…reviewed research and consensus statements before and after this meeting by to ensure that all elements involved in the use of body mass changes for assessing hydration status were included in the survey. 1,3,5,11,[17][18][19][20][21][22] Questions were developed that asked the AT to report his or her current practice for each implementation element. The panel members added and revised the survey until they agreed that the survey contained all of the implementation elements.…”
Section: Measurements and Instrumentationmentioning
confidence: 99%